Prognostic Value of QFR Measured Immediately After Successful Stent Implantation: The International Multicenter Prospective HAWKEYE Study - Biscaglia, Simone; Tebaldi, Matteo; Brugaletta, Salvatore; Cerrato, Enrico; Erriquez, Andrea; Passarini, Giulia; Ielasi, Alfonso; Spitaleri, Giosafat; Di Girolamo, Domenico; Mezzapelle, Giuseppe; Geraci, Salvatore; Manfrini, Marco; et al. (JACC. Cardiovascular interventions, 2019)
The aim of this study was to investigate the potential role of post-percutaneous coronary intervention (PCI) quantitative flow ratio (QFR) measurements to predict clinical outcomes in patients with successful PCI. The prognostic value of QFR measured immediately after PCI has not been prospectively investigated. Patients undergoing complete revascularization with successful PCI and stent implantation were eligible for acquisition of projections for QFR computation. At the end of the procedure, 2 angiographic projections for each vessel treated with PCI were acquired. Computation of QFR was performed offline by an independent core laboratory. The primary outcome was the vessel-oriented composite endpoint, defined as vessel-related cardiovascular death, vessel-related myocardial infarction, and ischemia-driven target vessel revascularization. Seven hundred fifty-one vessels in 602 patients were analyzed. The median value of post-PCI QFR was 0.97 (interquartile range: 0.92 to 0.99). Lesion location in the left anterior descending coronary artery, baseline SYNTAX (Synergy Between PCI With Taxus and Cardiac Surgery) score, lesion length, and post-PCI diameter stenosis were found to be predictors of lower post-PCI QFR. Altogether, 77 events were detected in 53 treated vessels (7%). Post-PCI QFR was significantly lower in vessels with the vessel-oriented composite endpoint during follow-up, compared with those without it (0.88 [interquartile range: 0.81 to 0.99] vs. 0.97 [interquartile range: 0.93 to 0.99], respectively; p < 0.001). Receiver-operating characteristic curve analysis identified a post-PCI QFR best cutoff of ≤0.89 (area under the curve 0.77; 95% confidence interval: 0.74 to 0.80; p < 0.001). After correction for potential confounding factors, post-PCI QFR ≤0.89 was associated with a 3-fold increase in risk for the vessel-oriented composite endpoint (hazard ratio: 2.91; 95% confidence interval: 1.63 to 5.19; p < 0.001). Lower values of QFR after complete and successful revascularization predict subsequent adverse events (Angio-Based Fractional Flow Reserve to Predict Adverse Events After Stent Implantation [HAWKEYE]; NCT02811796).